Arisan as a platform for social-identity and consumerism in the postmodern era - Silviana Purwanti; Muhammad, Harry Isra (Faculty of Communications Science, Dr. Soetomo University, 2026)
This study examined the transformation of arisan, a traditional rotating savings and social gathering practice, into a platform for social identity construction and symbolic consumption among women in Samarinda, East Kalimantan. As a secondary city shaped by rapid urbanisation and a mining-driven economic boom, Samarinda presents a distinctive socio-demographic context where global consumer culture intersects with local communal traditions. Drawing on Thorstein Veblen’s theory of conspicuous consumption and Pierre Bourdieu’s concepts of symbolic capital and habitus, this study conceptualises arisan as a communicative arena in which social status, identity, and distinction are actively negotiated. Employing a descriptive qualitative approach, data were collected through semi-structured in-depth interviews, participant observation during Arisan activities, and analysis of social media content. The study involved 16 women aged 30–50 from two elite arisan groups, Ganbatte and Pretty Woman. The findings revealed a shift in arisan from a financial mutual-aid mechanism toward a performative social space characterised by exclusive membership, symbolic consumption, and digitally mediated visibility. While Ganbatte emphasised professional networking and subtle prestige, Pretty Woman foregrounds conspicuous consumption and leisure-based status display. Arisan facilitates ‘modern independence’ primarily through expanded social networks, symbolic mobility, and the freedom to publicly perform identity beyond domestic roles.